Structural-semantic and linguocultural peculiarities of medical terms with zoo- and phytocomponents (on the material of German language) - Suprynovich, Oksana E. (Journal of the Belarusian State University. Philology, 2024)
The medical terms of the German language with zoo- and phytocomponents are considered. Their structuralsemantic and linguistic-cultural features are revealed. Groups of zoonymic names (vertebrate animals (mammals, birds, amphibians), invertebrate animals (molluscs, worms, insects)) are established. General (poloneutral), mythological, and phytonymic names have been determined. A significant part of German medical terms (94 %) are complex nouns (composites) (79 % consist of two components, 15% consist of three and four components) is defined. The zoo- and phytocomponents in the vast majority of cases acts as the first component of compound words. Medical terms are used to designate diseases or its symptoms (62 %), organs and parts of the human body, diagnostic methods and treatment methods, medical instruments and units of measurement. We identified 27 % of cases of using zoo- and phytonymic names in literal and 73 % in figurative meanings. Metaphor is a characteristic feature of the medical terminology of the German language. The main types of metaphorical transfer include transfer by form and colour metaphor. Other types of metaphorical transfer are also presented (by association, function, action, tactile features). The discrepancy between the figurative meanings of medical terms and the zoo- and phytocomponents in the German and Russian languages indicates the national nature of the metaphor is emphasised.